2013
DOI: 10.1016/j.celrep.2013.08.032
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisomal Enzyme L-PBE Is Required to Prevent the Dietary Toxicity of Medium-Chain Fatty Acids

Abstract: Specific metabolic pathways are activated by different nutrients to adapt the organism to available resources. Although essential, these mechanisms are incompletely defined. Here, we report that medium-chain fatty acids contained in coconut oil, a major source of dietary fat, induce the liver ω-oxidation genes Cyp4a10 and Cyp4a14 to increase the production of dicarboxylic fatty acids. Furthermore, these activate all ω- and β-oxidation pathways through peroxisome proliferator activated receptor (PPAR) α and PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 63 publications
5
64
0
Order By: Relevance
“…Data were normalized against two reference housekeeping genes: beta-2 microglobulin (B2m) and hydroxymethylbilane synthase (Hmbs) which were chosen based on stable gene expression levels, based on our pilot study. Others have also found a stable invariant expression of these genes in the livers of other high fat diet-induced obesity mouse models and hepatic cells [24], [25], [26]. The PCR primers used to amplify each gene are: B2m F-5′-CCCCACTGAGACTGATACATACG-3′ R-5′-CGATCCCAGTAGACGGTCTTG-3′, Ccr7 F- 5′-GTACGAGTCGGTGTGCTTCAA-3′ R-5′-GGTAGGTATCCGTCATGGTCT-3′, Ccl19 F- 5′-GTGATGGAGGGGTCAGGA-3′ R-5′-GGGATGGGACAGCCTAAACT-5′, Ccl21 F-5′-GTGATGGAGGGGGTCAGGA-3′ R-5′-GGGATGGGACAGCCTAAACT-3′, Cxcl1 (KC) F- 5′-CTGGGATTCACCTCAAGAACATC-3′ R-5′-CAGGGTCAAGGCAAGCCTC-3′, Cxcl2/3 (Mip2) F-5′-CCACCAACCACCAGGCTAC-3′ R-5′-GCTTCAGGGTCAAGGGCAAA-3′, Hmbs F-5′-TGTGGTGGCGATGCTGAAA-3′ R-5′-TTGTCTCCCGTGGACATA-3′, Ifng F-5′-ATGAACGCTACACACTGCATC-3′ R-5′-CCATCCTTTTGCCAGTTCCTC-3′, Il10 F-5′-GCTCTTACTGACTGGCATGAG-3′ R-5′-CGCAGCTCTAGGAGCATGTG-3′, Il12a F-5′-CTGTGCCTTGGTAGCATCTATG-3′ R-5′-CGCAGAGTCTCGCCATTATGAT-3′, Il12b F-5′-CTCAGAAGCTAACCATCTCCTGG-3′ R-5′-CACAGGTGAGGTTCACTGTTTC-3′, Il18 F-5′-GACTCTTGCGTCAACTTCAAGG-3′ R-5′-CAGGCTGTCTTTTGTCAACGA-3′, Srebp1 F-5′-GCAGCCACCATCTAGCCTG-3′ R-5′-CAGCAGTGAGTCTGCCTTGAT-3′, Tnfa F-5′-CCCTCACACTCAGATCATCTTCT-3′ R-5′-GCTACGACGTGGGCTACAG-3′.…”
Section: Methodsmentioning
confidence: 95%
“…Data were normalized against two reference housekeeping genes: beta-2 microglobulin (B2m) and hydroxymethylbilane synthase (Hmbs) which were chosen based on stable gene expression levels, based on our pilot study. Others have also found a stable invariant expression of these genes in the livers of other high fat diet-induced obesity mouse models and hepatic cells [24], [25], [26]. The PCR primers used to amplify each gene are: B2m F-5′-CCCCACTGAGACTGATACATACG-3′ R-5′-CGATCCCAGTAGACGGTCTTG-3′, Ccr7 F- 5′-GTACGAGTCGGTGTGCTTCAA-3′ R-5′-GGTAGGTATCCGTCATGGTCT-3′, Ccl19 F- 5′-GTGATGGAGGGGTCAGGA-3′ R-5′-GGGATGGGACAGCCTAAACT-5′, Ccl21 F-5′-GTGATGGAGGGGGTCAGGA-3′ R-5′-GGGATGGGACAGCCTAAACT-3′, Cxcl1 (KC) F- 5′-CTGGGATTCACCTCAAGAACATC-3′ R-5′-CAGGGTCAAGGCAAGCCTC-3′, Cxcl2/3 (Mip2) F-5′-CCACCAACCACCAGGCTAC-3′ R-5′-GCTTCAGGGTCAAGGGCAAA-3′, Hmbs F-5′-TGTGGTGGCGATGCTGAAA-3′ R-5′-TTGTCTCCCGTGGACATA-3′, Ifng F-5′-ATGAACGCTACACACTGCATC-3′ R-5′-CCATCCTTTTGCCAGTTCCTC-3′, Il10 F-5′-GCTCTTACTGACTGGCATGAG-3′ R-5′-CGCAGCTCTAGGAGCATGTG-3′, Il12a F-5′-CTGTGCCTTGGTAGCATCTATG-3′ R-5′-CGCAGAGTCTCGCCATTATGAT-3′, Il12b F-5′-CTCAGAAGCTAACCATCTCCTGG-3′ R-5′-CACAGGTGAGGTTCACTGTTTC-3′, Il18 F-5′-GACTCTTGCGTCAACTTCAAGG-3′ R-5′-CAGGCTGTCTTTTGTCAACGA-3′, Srebp1 F-5′-GCAGCCACCATCTAGCCTG-3′ R-5′-CAGCAGTGAGTCTGCCTTGAT-3′, Tnfa F-5′-CCCTCACACTCAGATCATCTTCT-3′ R-5′-GCTACGACGTGGGCTACAG-3′.…”
Section: Methodsmentioning
confidence: 95%
“…Additional proof for the requirement of MFP1 to degrade DCA was provided by challenging MFP1 mice with an excess of medium chain fatty acids (coconut oil diet, enriched in C12 triglyceride) [125]. This caused very extensive liver pathology including inflammation and fibrosis leading to death within 3 weeks which was prevented by blocking ω-hydroxylation with 1-aminobenzotriazole.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Certainly, the assumption that the steatohepatitis in Acox1 -/-mice is mediated by DCA does not fit with the unaffected liver in Mfp1 -/-and Acaa1 -/-mice. On the other hand, the extensive liver degeneration in coconut oil treated Mfp1 knockouts which do accumulate DCA is not accompanied with steatosis [125]. It would therefore be informative to challenge mice that are supposed to have impaired DCA degradation such as L-Pex5 (or other Pex mice), Abcd3, Acox1 and Acaa1 knockouts with a coconut oil diet and compare their responses with Mfp1 -/-mice.…”
Section: The Hepatotoxicity Of Dcamentioning
confidence: 99%
See 1 more Smart Citation
“…The two probe sets indicating increased expression in Pex1-G844D homozygous relative to heterozygous mice represented the Cyp4a14 and Ufd1l genes. Investigators reported the Cyp4 gene family is transcriptionally regulated in a PPARα/PPARγ-dependent manner with the Cyp4a14 gene product being involved in omega-oxidation of fatty acids [45]. The Ufd1l (aka Ufd1) gene plays a critical role in endoplasmic reticulum (ER)-associated degradation (ERAD) and cholesterol metabolism [46].…”
Section: Resultsmentioning
confidence: 99%